2016
DOI: 10.3892/or.2016.5231
|View full text |Cite
|
Sign up to set email alerts
|

Expression of angiogenic growth factors VEGF, bFGF and ANG1 in colon cancer after bevacizumab treatment in vitro: A potential self-regulating mechanism

Abstract: The present study aimed to examine changes in the expression of angiogenic growth factors in vascular endothelial cells isolated from colon cancer after bevacizumab treatment in vitro, and to explore a potential mechanism of their self-regulation as a possible mechanism for antiangiogenic therapy failure in clinics. Vascular endothelial cells were isolated from tumors of colon cancer patients and transfected with recombinant adeno-associated virus type 2-vascular endothelial growth factor (VEGF) or pGIPZ-VEGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…treatment with LCL‐5‐FU alone in C26 colon carcinoma in vivo with its stimulatory effect on the intratumor production of VEGF . Nevertheless, previous data have shown that several anti‐VEGF therapies have limited effects on cancer progression as a result of compensatory upregulation of other proangiogenic proteins in the tumor microenvironment . In line with these findings, our data indicated that both combined liposomal treatments almost totally reduced not only the intratumor levels of VEGF but also the production of other important proangiogenic molecules, such as eotaxin and leptin (Table A).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…treatment with LCL‐5‐FU alone in C26 colon carcinoma in vivo with its stimulatory effect on the intratumor production of VEGF . Nevertheless, previous data have shown that several anti‐VEGF therapies have limited effects on cancer progression as a result of compensatory upregulation of other proangiogenic proteins in the tumor microenvironment . In line with these findings, our data indicated that both combined liposomal treatments almost totally reduced not only the intratumor levels of VEGF but also the production of other important proangiogenic molecules, such as eotaxin and leptin (Table A).…”
Section: Discussionsupporting
confidence: 87%
“…This finding might be correlated with the impact of these treatments on the neovascularization of C26 colon carcinoma tumors (Figure ). Thus, our data have shown that LCL‐SIM + LCL‐5‐FU slightly increased the expression levels of CD31, a marker for proliferating endothelial cells, as a result of inefficient suppression of proangiogenic protein bFGF in the tumor microenvironment . Additionally, LCL‐SIManteLCL‐5‐FU reduced intratumor formation of new blood vessels as a consequence of its decelerating effects on the production of all proangiogenic molecules (Figure and Table A).…”
Section: Discussionmentioning
confidence: 57%
“…20 However, drug resistance to bevacizumab or even tumor recurrence was found after clinical use in some cancers, which may be attributed to the compensatory upregulation of some other angiogenesis factors. [21][22][23] Fibroblast growth factor-2 (FGF-2) is one of the most important protumor angiogenesis factors 24 and can promote tumor neovascularization independent of VEGF. 25 It was reported that FGF-2 is a key contributor to bevacizumab resistance 26 and the drug resistance of chemotherapy in breast cancer and melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…87 Liu and co-workers investigated the changes in VEGF expression and its correlation with the expression of proangiogenic factors, including bFGF and Ang after treatment with angiogenesis inhibitors. 88 The results indicated that when VEGFR-2 was suppressed, upregulation of bFGF and Ang was detected. In addition, VEGFR-2 internalization and certain downstream signaling are controlled by EphB4.…”
Section: Compensatory Activation and Cross-talk Of Proangiogenic Factorsmentioning
confidence: 96%
“…The complex cross‐talk between them has implications for the design of multitarget angiogenesis inhibitors . Liu and co‐workers investigated the changes in VEGF expression and its correlation with the expression of proangiogenic factors, including bFGF and Ang after treatment with angiogenesis inhibitors . The results indicated that when VEGFR‐2 was suppressed, upregulation of bFGF and Ang was detected.…”
Section: Angiogenic Factors and Compensatory Pathwaymentioning
confidence: 99%